Gold Nanostar@Polyaniline Theranostic Agent with High Photothermal Conversion Efficiency for Photoacoustic Imaging-Guided Anticancer Phototherapy at a Low Dosage - Wang, Yuanzheng (American Chemical Society (ACS), 2022)
10.1021/acsami.2c05679